2019
DOI: 10.3390/en12040603
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Improved Sampling Concepts for Offshore Wind Turbine Fatigue Design

Abstract: Fatigue damage is a design-driving phenomenon for substructures of offshore wind turbines. However, fatigue design based on numerical simulations is quite uncertain. One main reason for this uncertainty is scattering offshore conditions combined with a limited number of simulations (samples). According to current standards, environmental conditions are sampled using a deterministic grid of the most important environmental conditions (e.g., wind speed and direction, significant wave height, and wave period). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…[173] introduced different load case reduction concepts, using Monte Carlo simulations, basing the number of simulations on either the probability of occurrence, the expected damage or the equivalence of load conditions. The sampling approaches proposed by [173] were validated by [174] on the basis of an extensive data set from the Northwind wind farm. The study demonstrated an improved performance compared to standard sampling methods.…”
Section: Load Cases Reductionmentioning
confidence: 99%
“…[173] introduced different load case reduction concepts, using Monte Carlo simulations, basing the number of simulations on either the probability of occurrence, the expected damage or the equivalence of load conditions. The sampling approaches proposed by [173] were validated by [174] on the basis of an extensive data set from the Northwind wind farm. The study demonstrated an improved performance compared to standard sampling methods.…”
Section: Load Cases Reductionmentioning
confidence: 99%
“…Improvements in materials and technologies in recent years have allowed for taller towers, longer blades, and more power output (Wiser et al, 2016;Enevoldsen and Xydis, 2019). Because of their large size and associated large loads, as well as the cyclic loading caused by their rotational operation, fatigue is a vital consideration in wind turbine design (Hübler et al, 2019). Turbines must be designed to operate without failure and with minimal maintenance for the duration of their lifetime, which is usually 20-25 years (Hu et al, 2016;Ziegler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…CC BY 4.0 License. is a vital consideration in wind turbine design (Hübler et al, 2019). Turbines must be designed to operate without failure and with minimal maintenance for the duration of their lifetime, which is usually 20-25 years (Hu et al, 2016;Ziegler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%